ANALISIS RUGI DAYA DI PENYULANG OEBUFU PT. PLN (PERSERO) ULP KUPANG MENGGUNAKAN ALGORITMA GENETIKA - Agusthinus S. Sampeallo; Wellem F. Galla; Dhanang H. L. Rohi (Universitas Nusa Cendana, 2021)
The distribution system has a very important role in distributing electrical energy to costumers. Power quality in distribution system can affect the flow of electric distribution. Increase of electrical power demand can affect to power distributing quality like power losses, voltage drop and lower power factor. Load increasing make a reactive current can be up when flow in high resistance conductor as an effect. Installation of capacitor in distribution system is a one of the most efficient method to power losses pressure. This study discusses the optimization of capacitors location and capacity. Genetic algorithm is using as an optimization method. Backward-Forward Sweep Method to be the method of power flow analysis before and after instalation of capacitors to see their effect. Result of genetic algorithm will compare with manual calculation of choosing capacitors to know how effectively of genetic algorithm. This scheme is tested in Feeder Oebufu on 20 kV distribution system under PT. PLN (Persero) ULP Kupang operation. The test divided into 4 case included: before installation, placement of 1 capacitor, 2 capacitors, and 3 capacitors. Best result got in 3 capacitors simulation. Before installastion of capacitor, the power losses is 771,9928 kW, voltage minimum is 0,9842 pu, and power factor is 0,91257. Placement of 3 capacitors on bus 131 127, and 64 decrease a total power losses to be 31,164 kW, in other hand increase voltage profile around bus locations and power factor to be 0,99257.